2013
DOI: 10.2214/ajr.12.8877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dual-Energy Subtraction and Electronic Bone Suppression Combined With Computer-Aided Detection on Chest Radiographs: Effect on Human Observers' Performance in Nodule Detection

Abstract: very few series have dealt with a combination of these techniques [14,15]. The feasibility of software-only bone suppression on conventional chest radiography in combination with CAD has not been tested to date. Furthermore, of the studies in the literature, most investigators selected image collections in which each image contained only one lesion, a scenario that often does not correspond to the patient collective encountered during daily routine.The aim of the current investigation was to compare the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…A recent study reported that use of OnGuard, version 5.1, can significantly improve the sensitivity of human observers for the detection of 5-to 29-mm lung nodules in a selected patient data set (12). A more recent study reported that the same CAD system used in the present study improved radiologists' performance in the detection of solitary lung nodules on 111 PA CXRs, even when baseline performance was optimized by providing lateral radiographs and BSI images (13).…”
Section: Many Cad Systems Have Been Developed For the Detection Of Brmentioning
confidence: 57%
See 2 more Smart Citations
“…A recent study reported that use of OnGuard, version 5.1, can significantly improve the sensitivity of human observers for the detection of 5-to 29-mm lung nodules in a selected patient data set (12). A more recent study reported that the same CAD system used in the present study improved radiologists' performance in the detection of solitary lung nodules on 111 PA CXRs, even when baseline performance was optimized by providing lateral radiographs and BSI images (13).…”
Section: Many Cad Systems Have Been Developed For the Detection Of Brmentioning
confidence: 57%
“…Software BSI techniques (9)(10)(11)(12)(13)(18)(19)(20) can retrospectively create an image from a standard CXR that is similar to the soft-tissue image generated by a dedicated DES radiography unit. In a previous study with an early version of the CAD system, the CAD detection rate was 46% with 2.4 FPs per image on standard CXRs compared to 67% with 1.6 FPs per image on DES soft-tissue images (21) generated by a dedicated DES unit; however, such DES devices are not routinely available in clinical practice.…”
Section: Many Cad Systems Have Been Developed For the Detection Of Brmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many methods to improve detection of lung nodules on chest radiographs such as computer-aided diagnosis, and the removal or suppression of bony and other anatomical structures (28)(29)(30)(31)(32)(33). However, the clinical usefulness and cost-benefit of these techniques for detecting lung cancer remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there are far fewer poor-quality CXRs produced nowadays. Capturing CXRs in digital form has enabled further advances such as three-dimensional (3D) imaging using two or more spatially separated views, tomographic imaging using multiple views to generate one data set from which slices through the chest can be imaged individually and dual energy images to enable the separation of bony structures from soft tissues 2 3. These advances are yet to become standard practice, but are commercially available, and the masking of bony structures, particularly the ribs, has facilitated the development of computer-aided diagnosis for lung nodules.…”
Section: Evolution Of the Chest Radiographmentioning
confidence: 99%